Overall Survival in Aggressive B-Cell Lymphomas Is Dependent on the Accumulation of Alterations in p53, p16, and p27 - Sánchez-Beato, Margarita (American Society for Investigative Pathology, 2001)
Different studies have already shown that the isolated inactivation of p21, p16, or p27 cyclin-dependent kinase inhibitors (CKIs) is associated with increased growth fraction, tumor progression, or decreased overall survival in cases of non-Hodgkin’s lymphoma. In this study we linked molecular study of the p53 and p16 genes with immunohistochemical analysis of p27 expression in a group of aggressive B-cell lymphomas [large B-cell lymphomas (LBCLs) and Burkitt’s lymphomas]. This was done to analyze the relationship between p53 and p16 silencing, p27 anomalous overexpression, and clinical follow-up, testing the hypothesis that the accumulation of CKI alterations could confer to the tumors a higher aggressivity. In a group of 62 patients, p53 inactivation as a result of mutation was observed in 11 cases (18%) and p16 silencing was seen in 27 cases (43.5%) as a result of methylation (20 of 62), 9p21 deletion (7 of 44), or p16 mutation (2 of 62). The simultaneous inactivation of p53 and p16 was detected exclusively in five LBCL cases. Anomalous expression of p27, which has been proven to be associated with the absence of p27/CDK2 complexes and the formation of p27/cyclin D3 complexes where p27 is inactivated, was detected in 19 of 61 cases (31%). Cases characterized by p27 anomalous expression display concurrent inactivation of p21 (provided by p53 mutations) and/or p16 CKIs in 11 of 14 LBCL cases (P = 0.040). When the relationship between the association of inactivated CKIs and overall survival was considered, a significant relationship was found between a lower overall survival probability and an increased number of inactivated CKIs in LBCL cases, with the worst prognosis for the cases displaying concurrent p53, p16, and p27 alterations. This proves that simultaneous inactivation of different tumor suppressor pathways does indeed take place, and that tumor aggressiveness takes advantage of this CKI-concerted silencing. In this same series of data, Burkitt’s lymphoma patients seem to behave in a different way than LBCLs, with p53 and p16 alteration being mutually exclusive and the association with p27 anomalous expression not being clinically significant. These facts seem to support that the additive effect of the inactivation of different CKIs could be dependent of the histological type.